A Review Study for Robotic Exoskeletons Rehabilitation Devices - Alrawi, Rrafal; Sadik Aboud, Wajdi; Mohamed Haris, Sallehuddin (Al-Nahrain Journal for Engineering Sciences, 2023)
Nowadays, robotic exoskeletons demonstrated great abilities to replace traditional rehabilitation processes for activating neural abilities performed by physiotherapists. The main aim of this review study is to determine a state-of-the-art robotic exoskeleton that can be used for the rehabilitation of the lower limb of people who have mobile disabilities as a result of stroke and musculoskeletal conditions. The study presented the anatomy of the lower limb and the biomechanics of human gait to explain the mechanism of the limb, which helps in constructing a robotic exoskeleton. A state-of-the-art review of more than 100 articles related to robotic exoskeletons and their constructions, functionality, and rehabilitation capabilities are accurately implemented. Moreover, the study included a review of upper limb rehabilitation that has been studied locally and successfully applied to patients who exhibited significant improvements. Results of recent studies herald an abundant future for robotic exoskeletons used in the rehabilitation of the lower extremity. Significant improvement in the mechanism and design, as well as the quality, were observed. Also, impressive results were obtained from the performance when used by patients. This study concludes that working and improving the robotic devices continuously in accordance with the cases are necessary to be treated with the best results and the lowest cost.